Cholesterol in the viral membrane is a molecular switch governing HIV-1 Env clustering - Nieto-Garai, Jon Ander; Arboleya, Aroa; Otaegi, Sara; Chojnacki, Jakub; Casas, Josefina; Fabriàs, Gemma; Contreras, F-Xabier; Kräusslich, Hans-Georg; Lorizate, Maier (Advanced science, 2021)
HIV-1 entry requires the redistribution of envelope glycoproteins (Env) into a cluster and the presence of cholesterol (chol) in the viral membrane. However, the molecular mechanisms underlying the specific role of chol in infectivity and the driving force behind Env clustering remain unknown. Here, gp41 is demonstrated to directly interact with chol in the viral membrane via residues 751-854 in the cytoplasmic tail (CT751-854). Super-resolution stimulated emission depletion (STED) nanoscopy analysis of Env distribution further demonstrates that both truncation of gp41 CT751-854 and depletion of chol leads to dispersion of Env clusters in the viral membrane and inhibition of virus entry. This work reveals a direct interaction of gp41 CT with chol and indicates that this interaction is an important orchestrator of Env clustering.
First published: 21 December 2020
Gesehen am 23.11.2023